THEOLOGY OF THE CROSS IN AFRICAN EVANGELICALISM: IMPLICATIONS FOR CONTEMPORARY CHRISTIANITY - Isaac Boaheng (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
: It is not accidental that the cross is used as the symbol for Christianity. The cross actually epitomizes the execution of God’s salvific plan for humanity through the life, ministry and crucifixion of Jesus, the Christ. As the African church strives to contextualize the Christian faith and make it more meaningful and relevant to the existential realities of the African society, there is the need to develop and promote a Christian theology of the cross from both biblical and African religio-cultural perspectives. This paper addresses this theological need by exploring how an understanding of the theology of the cross from an African evangelical Christian perspective might function to decolonize Christianity and consequently, facilitate the spiritual growth of African believers. A literature-based research methodology was used to analyze data obtained from books, journal articles and theses/dissertations related to the subject matter. The paper concluded with implications of the theology of the cross for the ecumenical Christian community.